Tingkat Pelayanan Serta Ketersediaan Sarana Dan “Prasarana Pejalan Kaki Di Pantai Panjang Kota Bengkulu - Citra Arinesta; Elly Tri Pujiastuti (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2020)
Abstract Pantai Panjang is the leading tourism icon in the city of Bengkulu with an ever increasing number of visitors each year. Pantai Panjang already has special facilities in the form of roads intended of pedestrian. However for the criteria or standard of comfort for pedestrian paths in Pantai Panjang is unknown. In calculating the level of service using qualitative data analysis methods base on interpretation of actual condition. This research was conducted in two places in Pantai Panjang, namely the Spot Center Area and the Berkas Park. In each area devided in to three segment that is starting from 16.00 to 18.00 with the duration 15 minutes for each study. The results obtained indicate that the level of pedestrian infrastructure service are B (good) that the service level based on speed is 0.9 (seconds), current is 0.3 (people / m/second), density is (people/m2). The infrastructure availability for pedestrian in Spot Centre and Berkas Park still fill the road users need.